The evolution of Korean industrial and employment relations - Yi, Yŏng-myŏn 1960-; Kaufman, Bruce E. (EE, Edward Elgar Publishing, 2018)
The Evolution of Korean Industrial and Employment Relations explores current employment and workplace relations practice in South Korea, tracing their origins to key historical events and giving cultural, politico-economic and global context to the inevitable cultural adaptation in one of Asia's 'miraculous' democracies.